Pterostilbene protects against lipopolysaccharide-induced inflammation and blood–brain barrier disruption in immortalized brain endothelial cell lines in vitro - Yan Zhou; Yifan Yang; Rui Tian; Wai San Cheang (Scientific Reports)
Abstract Brain microvascular endothelial cells are connected by tight junction (TJ) proteins and interacted by adhesion molecules, which participate in the selective permeability of the blood–brain barrier (BBB). The disruption of BBB is associated with the progression of cerebral diseases. Pterostilbene is a natural compound found in blueberries and grapes with a wide range of biological activities, including anti-inflammatory, antioxidant, and anti-diabetic effects. In this study, we investigated the protective effects of pterostilbene on LPS-stimulated mouse brain endothelial (bEnd.3) cells and underlying mechanisms. The results showed that pterostilbene effectively upregulated the expressions of tight junction (TJ) proteins such as zonula occludens (ZO)-1 and claudin-5 and downregulated the expression of adhesion molecules such as intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1, preventing BBB damage under LPS stimulation. Pterostilbene decreased the LPS-triggered expressions of inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2 as well as the levels of interleukin (IL)-6, tumor necrosis factor (TNF)-α and nitric oxide (NO). Meanwhile, we found that pterostilbene exerted an inhibitory effect on nuclear factor kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways in bEnd.3 cells upon LPS stimulation. Additionally, pterostilbene exhibited antioxidant effects by activating heme oxygenase 1 (HO-1). These findings indicated that pterostilbene protected against lipopolysaccharide (LPS)-induced inflammation, oxidative stress and blood–brain barrier (BBB) disruption in bEnd.3 cells.